DEVELOPMENT OF PROBLEM-BASED TEACHING MATERIALS FOR THE FIFTH GRADERS OF PRIMARY SCHOOL - Yanti Fitria; Idriyeni Idriyeni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
Due to the importance of attractive learning materials in achieving a qualified learning results, it needs to carry on the development of the materials. The aim of this research is to develop science teaching materials using problem-based-learning model for primary school students. The developed teaching materials should strengthen the students' knowledge and thinking skills. This research and development refers to Thiagarajan model, consisting of defining, designing, developing, and dessiminating stage. The defining stage is conducted to have curriculum analysis, needs analysis, concept analysis and student analysis. At the designing stage, the researchers design the teaching materials. At the next stage, the proposed teaching materials are tested in terms of validity and practicality through validation sheet and questionnaire response of teachers and students. At the dessiminating stage, the researchers conduct a limited-scale deployment to notify the effectiveness of teaching materials on the achievement of activities and student learning outcomes. As the result, it indicates that the problem-based-teaching materials obtain high validity, practicality, and effectiveness.